HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN PENYESUAIAN SOSIAL PADA MAHASISWA BARU YANG BERASAL DARI LUAR KOTA SURABAYA - Elizabeth Findriany Tionardi (Perpustakaan Universitas Surabaya, 2018)
New student who comes from outside the city will find many difficulties like adjusting to the new environment. One of the important adjustment that new student need to have is social adjustment. The aim for this research is to determine the relationship between social support from peers with social adjustment on new students at faculty of Psychology, University of Surabaya, class of 2017 and comes from outside the city of Surabaya. Respondents obtained in this research is 85 new students in faculty of Psychology that comes from outside the city of Surabaya. The data was collected by using questionnaire consisting of three parts, namely open questionnaire containing identity and open question and closed questionnaire in the form of social adjustment scale and social support scale. Data analysis using social adjustment theory. Statistical test using Pearson correlation test. The results of the analysis show that research hypothesis is accepted, that there is a positive correlation between the two variables (r = 0,539; sig = 0,000). This shows the higher the social support received by students, the higher the social adjustment they have.